MECHANICAL AND PHARMACOLOGICAL SUPPORT OF BLOOD CIRCULATION IN SURGICAL TREATMENT OF LEFT VENTRICLE POSTINFARCTION ANEURISMS - V. V. Vitsukaev; V. N. Zavgorodny; V. N. Poptsov; D. V. Shumakov (Вестник трансплантологии и искусственных органов)
Despite all successes of a modern heart surgery, anesthesiology and resuscitation till now actual there is a ques- tion of improvement of results of surgical treatment of patients with chronic left ventricle postinfarction aneu- risms. Аfter left ventricular reconstructive surgery preoperative risk factors of development heavy myocardial dysfunctions in the postoperative period aren’t defined accurately now. We have made the analysis of 168 similar operations and have defined preoperative risk factors of development of severe heart failure in the intraoperative and early postoperative period. We have suggested methods to improve the results of operations in these patients using mechanical and pharmacological support of blood circulation. Use our suggested methods of preoperative preparation (Intraaortic balloon counterpulsation (VABK) and VABK + levosimendan) had significantly impro- ved results and significantly reduce mortality in patients with high risk of surgical treatment.